Analisis PPh Pasal 21 Sebelum dan Sesudah Menggunakan Tarif Efektif PP 58/2023 - Brigitha Alexandra Titis Yolanda; Erna Sulistyowati (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This research compares the calculation of Article 21 income tax based on Law Number 7 of 2021 concerning Harmonization of Tax Regulations with the calculation after the enactment of Government Regulation Number 58 of 2023 (PP 58/2023). In addition, this study also discusses the Minister of Finance Regulation Number 168 of 2023 (PMK 168/2023). The results show that with the application of the Effective Tariff (TER), the monthly tax imposition on individual taxpayers is lower than the calculation based on the HPP Law 7/2021. The research method used is descriptive qualitative, by collecting data and information from various sources, including relevant laws and regulations and analyzing tax calculations. This research is expected to provide a deeper insight into the impact of regulatory changes on the tax burden borne by individual taxpayers.